2020
DOI: 10.1155/2020/9149762
|View full text |Cite
|
Sign up to set email alerts
|

Role of Secreted Frizzled-Related Protein 1 and Tumor Necrosis Factor-α (TNF-α) in Bone Loss of Patients with Rheumatoid Arthritis

Abstract: Bone loss is one of the emerging extra-articular manifestations of rheumatoid arthritis. TNF-α is the main inflammatory cytokine that can directly increase bone resorption. However, its role in bone formation is still unknown, especially related to secreted frizzled-related protein 1 (SFRP-1), an osteoblast inhibitor. This study examines the correlation between TNF-α and SFRP-1, with a bone turn over marker (CTX and P1NP). This is a cross-sectional study with 38 subjects of premenopausal female patients with R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…IL17, in physiological conditions, is involved in defending epithelia and mucous membranes against bacteria and fungi, but it is overexpressed and seems to play an important role in inflammatory diseases like RA and spondyloarthritis (SpA); it was suggested that IL17-A is involved in the alteration of bone homeostasis in inflammatory arthritis by acting on osteoclast and osteoblast related pathways. In vitro stimulation of osteoblasts with IL17-A enhances sFRP1, a Wnt pathway antagonist, inhibiting osteoblasts formation [ 98 ]. Actually, the effects of IL17-A on osteoblasts in in vitro models are not always homogeneous [ 99 ], and the role of IL17 family in bone remodeling is still not clear and needs for further investigations, but its overexpression in pathologic conditions is harmful to bone homeostasis.…”
Section: Osteoblast Role In Ramentioning
confidence: 99%
“…IL17, in physiological conditions, is involved in defending epithelia and mucous membranes against bacteria and fungi, but it is overexpressed and seems to play an important role in inflammatory diseases like RA and spondyloarthritis (SpA); it was suggested that IL17-A is involved in the alteration of bone homeostasis in inflammatory arthritis by acting on osteoclast and osteoblast related pathways. In vitro stimulation of osteoblasts with IL17-A enhances sFRP1, a Wnt pathway antagonist, inhibiting osteoblasts formation [ 98 ]. Actually, the effects of IL17-A on osteoblasts in in vitro models are not always homogeneous [ 99 ], and the role of IL17 family in bone remodeling is still not clear and needs for further investigations, but its overexpression in pathologic conditions is harmful to bone homeostasis.…”
Section: Osteoblast Role In Ramentioning
confidence: 99%
“…Therefore, SFRP1 is considered a Wnt signaling pathway antagonist, which in turn interfere with Wnt signaling transduction and plays an important role in determining cell fate by regulating cell proliferation, differentiation, apoptosis, and pyroptosis ( 11 ). This regulation has also been studied in RA-FLS ( 12 ). In addition, some studies have found that SFRP1 can bind to recombinant A disintegrin and metalloproteinase 10 (ADAM10) protein and downregulate its activity in the Notch signaling transduction pathway, thus blocking the activation of Notch signaling ( 13 ).…”
Section: Introductionmentioning
confidence: 99%